Strength training biomechanics concept for athletic training systems - Samsonova, A.V.; Ponomarev, G. N.; Tsipin, L. L.; Bogdanov, O. A. (Theory and Practice of Physical Culture, 2018)
The study considers the following two aspects of strength trainings: skeletal muscle strength building concept; and strength exercise combination concept. Many study reports have found that the muscle strength growth is associated with minor damages and inflammation processes. There are a few assump-tions in this context needed to be checked by an experiment including: close-up aerobic trainings with fast walking or jogging are not recommended after intensive strength trainings; and anti-oxidizing agents are not recommended too. The immunity sags reported in athletes after high-intensity strength trainings may be due to the myogenic leukocytosis associated with the inflammation process in the muscles. The second recommendation on how the strength building exercises should be combined implies that they should be close to the competitive routines. In addition to the common principles of synergized effects, dynamic matching, progressive movement biomechanics and specific effects - we believe that the exercises should be composed with competitive routine stereotypes and compositions being taken into account based on the differentiated biomechanics matching principle. Depending on the specific sport discipline, the latter principle implies the relevant sensor, kinematic and dynamic patterns of competitive routines and special training exercises being harmonized to secure the focus on the core muscle groups in the trainings.